PENGARUH KUALITAS PELAYANAN DAN KEPERCAYAAN TERHADAP KEPUASAN MASYARAKAT DALAM PENGGUNAAN APLIKASI JAKEVO DI KELURAHAN PULO, JAKARTA SELATAN - Suhalya, Sarah; Samsudin, Samsudin (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
The Province of DKI Jakarta introduced a service innovation through the Jakarta Evolution (Jakevo) application on April 26, 2018, which facilitates the public in managing licensing and non-licensing services efficiently and practically. The aim of this research is to analyze the effect of service quality and public trust, both partially and simultaneously, on public satisfaction in using the Jakevo application in Kelurahan Pulo, South Jakarta. This study employs a quantitative descriptive research method, with data collected through questionnaires. The population in this study consists of 103 individuals who applied for licensing services through the Jakevo application in Kelurahan Pulo from March 2023 to March 2024. A sample of 50% of the population, or 52 respondents, was used. The results indicate that Service Quality has a positive and significant influence of 60.5% on Public Satisfaction in Kelurahan Pulo, while Public Trust has an influence of 77.5%. Service Quality and Public Trust simultaneously have a positive and significant effect of 79.5% on Public Satisfaction, while the remaining 20.5% is influenced by other variables not examined in this study.